DEVELOPMENT OF ETNOSAINS-BASED IPA LKPD ON LIVING CLASSIFICATION MATERIALS INTEGRATED CRITICAL THINKING ABILITY OF CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Sustri Wahyuni; Tuti Lestari (Department of Science Education, 2021)
This study aims to analyze the validity and practicality of the ethnoscience-based LKPD that has been developed for junior high school students. This type of research is development or Research and Development with a 4-D model with ethnoscience-based LKPD objects. The research data is in the form of qualitative data obtained from a questionnaire given to the research subjects, namely teachers and lecturers and analyzed with a Likert scale. The aspects that are assessed by the validator in the validity analysis are the content feasibility component, presentation component, linguistic component, and graphic component. Whereas in the practical analysis, namely ease of use, efficiency of study time, benefits. The results of the study are that the ethnoscience-based LKPD on the integrated material classification of critical thinking skills developed can be used and practical in science learning in schools.